2017
DOI: 10.3847/1538-4357/aa94c2
|View full text |Cite
|
Sign up to set email alerts
|

The Circumstellar Disk HD 169142: Gas, Dust, and Planets Acting in Concert?*

Abstract: HD 169142 is an excellent target for investigating signs of planet-disk interaction due to previous evidence of gap structures. We perform J-band (∼1.2 μm) polarized intensity imaging of HD 169142 with VLT/SPHERE. We observe polarized scattered light down to 0 16 (∼19 au) and find an inner gap with a significantly reduced scattered-light flux. We confirm the previously detected double-ring structure peaking at 0 18 (∼21 au) and 0 56 (∼66 au) and marginally detect a faint third gap at 0 70-0 73 (∼82-85 au). We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
82
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 111 publications
6
82
1
Order By: Relevance
“…According to Panić et al (2008) observations in the 1.3 mm dust continuum and CO (J = 2 − 1) emission line the disc has an inclination of 13 degrees, a position angle of 5 degrees and a total gas mass of ∼ 0.6 − 3.0 × 10 −2 M , confirmed by subsequent observations (Fedele et al 2017;Perez et al 2019, hereafter FD17 and PS19). This source has been observed in the thermal mid-infrared emission (Honda et al 2012), near-infrared emission (Reggiani et al 2014;Pohl et al 2017;Ligi et al 2018;Bertrang et al 2018), near-infrared polarimetric and scattered light images (Pohl et al 2017). Gas and dust are physically decoupled in HD 169142.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…According to Panić et al (2008) observations in the 1.3 mm dust continuum and CO (J = 2 − 1) emission line the disc has an inclination of 13 degrees, a position angle of 5 degrees and a total gas mass of ∼ 0.6 − 3.0 × 10 −2 M , confirmed by subsequent observations (Fedele et al 2017;Perez et al 2019, hereafter FD17 and PS19). This source has been observed in the thermal mid-infrared emission (Honda et al 2012), near-infrared emission (Reggiani et al 2014;Pohl et al 2017;Ligi et al 2018;Bertrang et al 2018), near-infrared polarimetric and scattered light images (Pohl et al 2017). Gas and dust are physically decoupled in HD 169142.…”
Section: Introductionmentioning
confidence: 88%
“…Many authors (FD17, Pohl et al 2017;Ligi et al 2018;Bertrang et al 2018, ME18, PS19) pointed out the presence of giant planets in the disc (M > few Jupiter masses, hereafter M J ), an inner one located inside the inner dust cavity (R < 20 au) and an outer one in the gap between the two dust rings (35 < R < 55 au) to explain the signature double-ring morphology. The splitting of the outer ring in concentric rings have been modeled by PS19 with the presence of a single migrating low mass planet (∼ 10 −2 M J ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the millimeter observations by Guilloteau et al (2011) constrained the disk inclination to only ∼ 65 • , implying that the disk opening angle for small particles in the outer regions is larger than 90 • − 65 • = 25 • . In several Class II sources with more inclined disks, the star is not obscured by the disk (see, e.g., Pohl et al 2017;Langlois et al 2018;Avenhaus et al 2018). This implies that the earlytype SED of DG Tau B is due to its young evolutionary stage and not by a coincidental alignment of disk and line of sight.…”
Section: Introductionmentioning
confidence: 97%
“…ALMA has confirmed that TDs are a very diverse set of protoplanetary disks, for which several gas and dust morphologies have been observed. Complementary to ALMA data, extreme adaptive optics and coronagraphic observations at optical and near-infrared wavelengths have also enriched our knowledge of the TDs structures (e.g., Follette et al 2013;Avenhaus et al 2014;de Boer et al 2016;Pohl et al 2017a). The combination of high-resolution observations at different wavelengths has shown how the distribution of micron-sized particles traced at short wavelengths can significantly differ from the distribution of millimeter-sized particles (e.g., Garufi et al 2013;Pinilla et al 2015b;Hendler et al 2018).…”
Section: Introductionmentioning
confidence: 98%